Village’s Digital Capital: Positioning and Implementation Concept - Rahmawati, Emma; Faubiany, Varenna; Aldha Mauliddina Siregar, Nurul; Daniarta Sukarno, Taufan (Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
The progress of a region cannot be separated from the development of digitalization. Now, digitalization is very important in development, because it is a capital that interacts with five offline capitals as social capital, economic capital, personal capital, political capital, and cultural capital owned by the community so that it will improved welfare, income, health, and others. Digital village is an idea that is being proclaimed by local government in collaboration with rural government. Punggul village Badung Region and Beraban village Tabanan Region in Bali Province already programmed digital village in their village development. The purpose of this research is to describe how digitalization is applied in services to the community and village development and how to carry out digitalization as a capital carried out by the Punggul and Beraban Village Governments. This research uses qualitative research methods with case study. Data collecting methods uses interview, observation, and documentation. This research result show us about the position interaction between digital capital and five offline capitals in Punggul village and Beraban village the same is in “the third level of digital divide” which internet used driven by and for the increasing offline capital. While the relationship between digital capital and five offline capital, the Punggul village is the ideal type and Beraban village is the third level of ideal scenario. Digitalization in both of villages become a supportive capital in improving villagers welfare.